Regional Implications of Financial Market Development: Credit Rationing, Trade, and Location - Tobias Seidel; Maximilian von Ehrlich (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We develop a heterogeneous-fi rms model with trade in goods, labor mobility and credit constraints due to moral hazard. Mitigating fi nancial frictions reduces the incentive of high-skilled workers to migrate to one region such that an unequal distribution of industrial activity becomes less likely. Hence, financial market development has opposite regional implications as trade liberalization. While the former leads to more dispersion of economic activity across space, the latter tends to drive clustering. We provide empirical evidence for this hypothesis by combining industry-region variation in the spatial concentration of economic activity with information on the access to credit and the dependence on external finance. Our estimates for 20 European countries and eleven industries con firm that fi nancial market development mitigates the clustering of economic activity.
Keywords: F12; F36; R11; 330